Efavirenz Pharmacokinetics and Human Immunodeficiency Virus Type 1 (HIV-1) Viral Suppression Among Patients Receiving Tuberculosis Treatment Containing Daily High-Dose Rifapentine . (16th December 2021) - Podany, Anthony T; Pham, Michelle; Sizemore, Erin; Martinson, Neil; Samaneka, Wadzanai; Mohapi, Lerato; Badal-Faesen, Sharlaa; Dawson, Rod; Johnson, John L; Mayanja, Harriet; Lalloo, Umesh; Whitworth, William C; et al.
Abstract: Background: A 4-month regimen containing rifapentine and moxifloxacin has noninferior efficacy compared to the standard 6-month regimen for drug-sensitive tuberculosis. We evaluated the effect of regimens containing daily, high-dose rifapentine on efavirenz pharmacokinetics and viral suppression in patients with human immunodeficiency virus (HIV)-associated tuberculosis (TB). Methods: In the context of a Phase 3 randomized controlled trial, HIV-positive individuals already virally suppressed on efavirenz–containing antiretroviral therapy (ART) (EFV1), or newly initiating efavirenz (EFV2) received TB treatment containing rifapentine (1200 mg), isoniazid, pyrazinamide, and either ethambutol or moxifloxacin. Mid-interval efavirenz concentrations were measured (a) during ART and TB cotreatment (Weeks 4, 8, 12, and 17, different by EFV group) and (b) when ART was taken alone (pre- or post-TB treatment, Weeks 0 and 22). Apparent oral clearance (CL/F) was estimated and compared. Target mid-interval efavirenz concentrations were > 1 mg/L. Co-treatment was considered acceptable if > 80% of participants had mid-interval efavirenz concentrations meeting this target. Results: EFV1 and EFV2 included 70 and 41 evaluable participants, respectively. The geometric mean ratio comparing efavirenz CL/F with vs without TB drugs was 0.79 (90% confidence interval [CI] .72–.85) in EFV1 and 0.84 [90% CI .69–.97] in EFV2. The percent of participants with mid-interval efavirenz concentrations > 1mg/L in EFV1 at Weeks 0, 4, 8, and 17 was 96%, 96%, 88%, and 89%, respectively. In EFV2, at approximately 4 and 8 weeks post efavirenz initiation, the value was 98%. Conclusions: TB treatment containing high-dose daily rifapentine modestly decreased (rather than increased) efavirenz clearance and therapeutic targets were met supporting the use of efavirenz with these regimens, without dose adjustment. Clinical Trials Registration: NCT 02410772. Abstract : The use of rifamycin antibiotics is often complicated by clinically relevant drug-drug interactions. We characterized the modest impact of rifapentine-based tuberculosis (TB) treatment on the pharmacokinetics and human immunodeficiency virus type 1 (HIV-1) viral suppression of efavirenz-based antiretroviral therapy.